Is it Possible to Define the Boundaries of Hate Speech? - Župerka, Kazimieras (Acta humanitarica academiae Saulensis, 2021)
During the last few years, a phrase hate speech has become widespread as an expression of a legal concept in the Lithuanian language. In the laws of the Republic of Lithuania, the concept of hate speech has not yet been precisely defined and directly established. The usage of the combination of these two words expands the concept of hate, it loses at least somewhat clearer boundaries. However, based on this concept, intentions are expressed to reinforce the laws of administrative law regarding manifestations of hate speech.In the article, the concept of the Lithuanian noun neapykanta (‘hate’) is explained by its usage in texts, the relationship between this word and other Lithuanian words with negative connotations has been analysed as well. The examples of unmeasured expansion of the concept of hate speech found in research works have been highlighted. Several more prominent cases of public speaking that had a wider resonance, which were associated with hate speech, are discussed from the point of view of language axiology.Since negative words with a softer definition are not considered at the same level as hate, then prescribing (to) bully, (to) make fun of, (to) push around, (to) intimidate, (to) tease (concept expressed in corresponding words) to the definition of hate is a conceptual mistake. These emotional and verbal or non-verbal speech concepts can be associated with hate but they can also be described as just emotions “until hate”.Replacing the compound speech that provokes hate with an abbreviated hate speech leads to confusion: different concepts are conflated, it becomes irrelevant, whether it is inciting hatred or just is associated with it – it still tends to be considered a crime (especially in cases where the case of public linguistic expression is related to the so-called vulnerable, protected groups of persons, for example, Gypsies/Roma, LGBT, migrants). Only the direct encouragement of hatred, the call for confrontation can be evaluated and more or less exactly formulated linguistically, and therefore, legally.
Keywords: hate; hate speech; homophobia